Design of an innovative linear Fresnel collector by means of optical performance optimization: A comparison with parabolic trough collectors for different latitudes. (1st September 2017) - Abbas, R.; Valdés, M.; Montes, M.J.; Martínez-Val, J.M.
Highlights: LFC solar fields are optimized for different latitude locations. NS orientation is adequate for low latitude; in high latitudes EW is recommended. EW embodiments require a lower number of mirrors, which reduces costs. EW embodiments can be tilted towards the south increasing the optical efficiency. For the studied locations, LFC performance is 20–30% lower than PTCs. Abstract: Different innovative linear Fresnel field designs are obtained for two locations of latitudes 37° N and 24° N. This designs are the result of the exergy efficiency optimization by means of a validated Monte Carlo Ray Trace code and analytic methods. From the results obtained it is concluded that, whereas for high latitude locations East-West orientation achieves higher efficiencies with lower cost, when the solar field is located in latitudes closer to the tropics NS orientation is a better solution. From the performance comparison between Fresnel and trough collectors it results that, although the latter always achieves higher exergy efficiencies, differences are importantly reduced for low latitudes.